A model of challenge funds: How funding availability and selection rigor affect project quality - Raphael Boleslavsky; Bruce Ian Carlin; Christopher Cotton (Queen's University, Department of Economics, 2021)
Challenge funds (CF) induce competition between grant applicants as they develop proposals to address important social problems. We develop a game theoretic model to study how funding availability and proof of concept requirements (e.g., pilots or other forms of early stage screening) influence investments by applicants and the ultimate success of the CF. Larger budgets and more rigorous proof of concept requirements can reduce applicant investments and lead to less effective funding initiatives. The results show how the design of a CF affect the incentives of those competing for funding, and how the most effective CF design needs to carefully consider how the NGOs or researchers applying for funding will respond to a change in incentives. Otherwise, steps taken to improve the quantity or quality of funded projects can backfire and decrease overall funding effectiveness.
Keywords: D83; O22; O35; H57; H83; H87; H43; 330; Challenge Funds; Grants; Project Evaluation; Pilot Studies; Funding Allocation; Evidence Based Funding